2016
DOI: 10.5505/tjtes.2016.77177
|View full text |Cite
|
Sign up to set email alerts
|

The geriatric polytrauma: Risk profile and prognostic factors

Abstract: BACKGROUND:In the German population, the percentage of elderly patients is increasing, and consequently there are more elderly patients among trauma cases, and particularly cases of polytrauma. The aim of this study was to present clinical results and a risk profile for geriatric polytrauma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 43 publications
0
20
0
1
Order By: Relevance
“…Although blood transfusion may indicate an important physiological response to a drop of systolic blood pressure or a risk associated with penetration injury, the use of BT as the sole physiological variable may not be accurate as that calculated from RTS, which is made up of three categories: Glasgow Coma Scale (GCS), systolic blood pressure, and respiratory rate [ 17 ]. A very low GCS score, a variable that is not used in the calculation of GTOS, is a strong clinical indicator of prognosis in patients with traumatic brain injury [ 18 ]. Patients with a GCS score below 12 was associated with a twofold increase in mortality rate (39% vs 83%) compared with those who had a GCS score equal or higher than 12 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although blood transfusion may indicate an important physiological response to a drop of systolic blood pressure or a risk associated with penetration injury, the use of BT as the sole physiological variable may not be accurate as that calculated from RTS, which is made up of three categories: Glasgow Coma Scale (GCS), systolic blood pressure, and respiratory rate [ 17 ]. A very low GCS score, a variable that is not used in the calculation of GTOS, is a strong clinical indicator of prognosis in patients with traumatic brain injury [ 18 ]. Patients with a GCS score below 12 was associated with a twofold increase in mortality rate (39% vs 83%) compared with those who had a GCS score equal or higher than 12 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…A very low GCS score, a variable that is not used in the calculation of GTOS, is a strong clinical indicator of prognosis in patients with traumatic brain injury [ 18 ]. Patients with a GCS score below 12 was associated with a twofold increase in mortality rate (39% vs 83%) compared with those who had a GCS score equal or higher than 12 [ 18 ]. Furthermore, the units of blood transfused may indicate profound hemorrhage shock.…”
Section: Discussionmentioning
confidence: 99%
“…Anti-platelet therapy, NACA score, initial GCS, ISS and age were risk factors for mortality. Several previous studies [7,18,[22][23][24][25][26][31][32][33] have described advanced age, along with higher ISS and lower GCS as being associated with trauma mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies de ned geriatric trauma patients as patients over the age of 65 years [11] .Due to geriatric patients generally decreased physiological reserves and suffered from underlying diseases,they were more susceptible for high mortality rate and fatal complications, particularly MODS [12] .Alteration in the cardiovascular and respiratory systems exacerbated the potential to hypoxia and shock,pre-existing conditions of the respiratory system increased the risk for pneumonia,as well as acute respiratory distress syndrome(ARDS) [11] .Despite the severity of the injury is equivalent,geriatric patients have worse outcome than younger patients [13] .A study reported by Aldrian showed that elderly patients with multiple trauma had a signi cantly higher incidence of MODS compared to younger group(17.8% vs 7.1%,p=0.02) [14] .Similarly,in our study the ratio of geriatric patients (age over 65 years) in MODS group had a signi cance higher than non-MODS group(31.7% vs 20.7%,p=0.009).…”
Section: Discussionmentioning
confidence: 99%